The potential of coconut oil as an anti-obesity agent: a scoping review - Duvadilan, Sakti Pratami; Rahmawati, Riana (Universitas Islam Indonesia, 2024)
Background: The rising global prevalence of obesity and its related health issues make it crucial to explore all potential therapeutic options. Coconut oil (CNO) has been extensively studied for its health benefits, yet no scoping review has specifically assessed its potential as an anti-obesity agent, particularly among obese subjects. Objective: This review aims to outline the characteristics and findings regarding the use of coconut oil as an anti-obesity agent in both experimental animal and human studies. Method: The review included original studies on the potential of coconut oil as an anti-obesity agent, published in English or Indonesian between 2011 and 2022. A comprehensive search was performed across databases such as PubMed, ScienceDirect, Google Scholar, SpringerLink, and Portal Garuda. Articles were selected following the PRISMA-ScR flow diagram, with subsequent data extraction, analysis, and synthesis conducted.Results: Eight articles met the inclusion criteria, comprising four preclinical trials (involving obese animal models) and four human studies that recruited obese people. The preclinical trials used virgin coconut oil (VCO), while the human studies utilized both VCO and coconut oil (CNO). In preclinical trials, VCO administration was associated with reductions in low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), and triglyceride (TG) levels. In clinical trials, consumption of VCO and CNO was linked to increased high-density lipoprotein cholesterol (HDL-C) levels and reductions in LDL-C, TC, TG, and anthropometric measures (body weight, body mass index, waist circumference, waist-to-hip ratio, and body fat mass). However, the effects of VCO and CNO on LDL-C, TC, and TG were inconsistent.Conclusion: Coconut oil, particularly in the form of VCO, has shown potential as a supplement for managing obesity. However, this scoping review highlights inconsistencies in the effects of coconut oil on lipid profiles (LDL-C, TC, TG), indicating the need for further research to clarify these outcomes.